Role of Notary in Criminal Justice Process - Rahmia Rachman; Titie Yustisia Lestari (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
The criminal justice process raises a conflict regarding the role of a Notary, who is a public official responsible for creating authentic deeds and is bound by confidentiality, yet is required to testify about the deeds they have made. This study examines the role of the Notary as a witness in criminal cases involving deeds they have created and the legal protection provided to Notaries when giving testimony. The research uses an empirical juridical approach, collecting primary data through field interviews and document studies. The findings reveal that the Notary’s role as a witness in criminal proceedings is crucial for investigations. Notaries summoned for investigation must first obtain approval from the Notary Honorary Council of the Region (MKNW) and provide information, both orally and in writing, at the trial. Notaries are called to participate in the examination of criminal cases in their capacity as public officials who create authentic deeds, and their testimony is essential regarding what they have seen, heard, and the supporting evidence in the creation of the authentic deed involved in the criminal case. The study also highlights the legal protection for Notaries as witnesses, including the requirement to obtain approval from the Notary Honorary Council of the Region (MKNW) through a written request with justifications. Furthermore, Notaries are protected under the rights and obligations outlined in Article 1909 paragraph (3) of the Civil Code and Article 322 of the Penal Code. This research contributes to a deeper understanding of the specific role of Notaries within the criminal justice system, an area that has been underexplored in existing literature, particularly in comparison to their role in civil matters. The study provides valuable insights into the legal challenges and protections faced by Notaries when testifying in criminal proceedings.